TINGKAT PENGETAHUAN, SIKAP DAN TINDAKAN KELUARGA PASIEN HEMODIALISIS MENGENAI GAGAL GINJAL KRONIK DI RSUD DOKTER SOEDARSO PONTIANAK - ., Devi Noviriyanti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. The number patients with Chronic Renal Failure (CRF)undergoing hemodialysis is increasing every year worldwide, including inIndonesia. Therefore, it is vital to do early prevention of kidney disease byidentifying risk factors and improving the knowledge, attitudes and actionsabout CRF. Objective. The aim of this study was to know the level ofknowledge, attitude, and action of hemodialysis patients relatives aboutchronic renal failure at dr. Soedarso General Hospital Pontianak Method.This research was a descriptive study with cross-sectional approach whichwas conducted by using questionnaires of 36 relatives of hemodialysispatients. Data was collected at hemodialysis room of dr. SoedarsoGeneral Hospital on September 2012 Result. Level of knowledge ofpatients relatives was 66,67% categorized as good, 27,78% moderate,and 5,55% categorized as less. The attitudes of patients relatives are66,67% categorized as good and 25% moderate and 8,33% categorizedas less. The action of patients relatives are 47,22% categorized as good,33,34% moderate, and 19,44% categorized as less. Conclusion. Thisresearch showed that most of hemodialysis patients relatives in dr.Soedarso General Hospital Pontianak was categorized as good for level ofknowledge, attitudes, and actions. Keywords: knowledge, attitude, action, CRF.